SEEDING RIDGE FORMING DIRECT PLANTING MACHINE - TSUCHIYA FUMINORI; KAWAMURA YOSHITERU; FUKAMI KOICHIRO; MIIKE TERUYUKI; ITO HIROTO; KAWAHARA YUKINARI (2016)
PROBLEM TO BE SOLVED: To perform new dry rice field direct planting in which the seeding ridge forming and direct seeding are performed in the same process, and thereby the production cost is reduced, the water leakage in a germinating initial stage is prevented and weed damage is prevented, and the feeding damage of apple snails causing a serious problem in the Kyushu area is avoided.SOLUTION: A seeding ridge forming direct planting machine 1 is mounted in the rear of a traveling machine body, and the seeding ridge forming and the direct seeding are performed in the same process while moving the field in a high soil water state. The seeding ridge forming direct planting machine includes multiple ridge forming units 3 equipped in a drive shaft 2 perpendicular to the traveling direction, and a direct seeding working unit 4 disposed in the front or rear in the traveling direction of the ridge forming unit 3. The ridge forming unit 3 includes a side surface forming unit 30 for forming the side surface of the seeding ridge of a trapezoidal cross-section shape, and a top surface forming unit 31 for forming the top surface of the seeding ridge. The side surface forming unit 30 and the top surface forming unit 31 include pressure coating bodies 30B, 31B for repeatedly making pressure coating of the side surface or the top surface of the seeding ridge by the rotation of the drive shaft 2. The direct seeding working unit 4 performs seeding on the top surface of the seeding ridge to be formed.SELECTED DRAWING: Figure 2 【課題】播種畝成形と直播を同工程で行う新たな乾田直播栽培を行うことで、生産コストを低減、発芽初期段階における漏水の防止や雑草害の防止、九州地域で深刻な問題になっているスクミリンゴ貝の食害回避を図る。【解決手段】走行機体の後方に装着され、高土壌水分状態の圃場を進行しながら播種畝成形と直播を同工程で行う播種畝成形直播機１であって、進行方向に直交する駆動軸２に装備される複数の畝成形部３と、畝成形部３の進行方向前方又は後方に配備される直播作業部４とを備え、畝成形部３は、台形断面形状の播種畝の側面を成形する側面成形部３０と播種畝の天面を成形する天面成形部３１を備え、側面成形部３０と天面成形部３１は、駆動軸２の回転で播種畝の側面或いは天面を繰り返し圧塗りする圧塗り体３０Ｂ，３１Ｂを備え、直播作業部４は、成形される播種畝の天面部に播種を行う。【選択図】図２